2012
DOI: 10.1590/s1808-18512012000400011
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between symptoms and sagittal alignment parameters in patients with lumbar canal stenosis: a case-control study

Abstract: Objective: To examine the relationship between sagittal balance parameters and different symptoms of spinal disease in patients with lumbar canal stenosis (LCS) and controls. Methods: In this prospective, diagnostic, case-control study, we included all patients consecutively admitted to a public teaching hospital for surgical treatment of LCS between July 2010 and October 2011, aged more than 40 years, with back pain plus radiculopathy or neurogenic claudication, and controls without LCS. Magnetic resonance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Of the 58 individuals had TK T4-T12 measured, 4 were hypokyphotic, 47 had normal kyphosis, and 7 were hyperkyphotic, considering normal to be between 20 and 40. 19 Table 5 shows the mean TK, ODI, VAS, and EQ-5D by TK classification group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 58 individuals had TK T4-T12 measured, 4 were hypokyphotic, 47 had normal kyphosis, and 7 were hyperkyphotic, considering normal to be between 20 and 40. 19 Table 5 shows the mean TK, ODI, VAS, and EQ-5D by TK classification group.…”
Section: Resultsmentioning
confidence: 99%
“…The same authors also found that the population of DLS patients was older than the randomly selected control group. 19 Several studies argue that an increase in SVA is associated with a poorer quality of life and an increase in axial pain. [23][24][25] In 2013, Schwab concluded that serious clinical disability (ODI > 40) is associated with an increase in SVA, PI-LL mismatch, and PT.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Rod molding, together with spinal fixation, influences the pelvic parameters. 23,24 The objective of our study was to evaluate pre-and postoperative parameters to determine whether the normal spinopelvic parameter and sagittal balance values were maintained. Comparing the mean variation in kyphosis became relevant, since there was a great variation in the range of the variable in both the pre-(6.6° -86.2°) and postoperative (18.2° -59.7°) periods; and, consequently, so did determining what type of influence this variation has on overall sagittal alignment with each group and in the comparison among them.…”
Section: Discussionmentioning
confidence: 99%
“…This change in the sacral slope, showing decreased values, negatively influences the clinical pain of the patients. 15 The decreased sacral slope, referring to the sacral standard similar to when we are seated, causes more pain post-surgery. 16 Therefore, we should be concerned with maintaining the sacral parameters within appropriate values.…”
Section: Time Of Evaluationmentioning
confidence: 99%
“…19 The molding of rods, along with the fixation of the spine, influences the pelvic parameters. 15 Another factor that can influence the pelvic parameters is the angle resulting from the positioning of the pelvis with the surgical pads, since the pelvic values are directly influenced by the positioning of the hip (center of the femoral head). 1…”
Section: Time Of Evaluationmentioning
confidence: 99%